Children's Perspectives on Fairness and Inclusivity in the Classroom. (2nd November 2022) - Kaufman, Elise Marie; Killen, Melanie
Abstract: School represents an important context for children's social, moral, and identity development. Research indicates that supportive teacher-student relationships are significantly related to positive student academic achievement. Unfortunately, teacher bias as well as peer exclusion based on group identity (gender, race, ethnicity, and nationality) pervade many school contexts. The presence of these biases in the classroom is negatively related to students' academic development, especially for children who are minoritized and marginalized. Very little research has connected teacher bias and children's reasoning about bias and inequalities in the classroom context. The classroom is a complex environment in which to examine children's social and moral reasoning about bias, given teachers' position of authority which often includes power, status, and prestige. We propose that understanding both teacher bias and peer intergroup exclusion are essential for promoting more fair classrooms. This paper reviews foundational theory as well as the social reasoning developmental model as a framework for studying how children think about fairness and bias in the classroom context. We then discuss current research on children's social-cognitive and moral capacities, particularly in the contexts of societal inequality and social inclusion or exclusion. Finally, this article proposes new directions for research to promote fairness and inclusivity in schools and suggests how these new lines of research might inform school-based interventions.